Time evolution of rain drop spectra over Cuddalore in coastal Tamilnadu (MAUSAM, 2004)
A disdrometer has been installed at Meteorological Office, Cuddalore in Coastal Tamilnadu during first week of April 2002. This paper attempts to describe an overview of the technicalities and facilities available in this disdrometer besides describing the results of the rain drop size distribution(DSD) from May to August 2002 covering parts of pre-monsoon (March – May) and southwest monsoon (June – September) season. The rain accumulation as measured by the disdrometer matches perfectly with the surface rain gauge measured amount for the rain rate upto 66 mm/hr. The contrasting features of rain spells over Cuddalore, a coastal station in southern peninsular India are clearly brought out in terms of DSDs albeit the rain amount during these period in the year 2002 was very subdued. The modal rain rate was less than 6 mm/hr (84% frequency) followed by 10-40 mm/hr (11%). The concentration of drops, specifically the concentration of larger drops, per rain spell is higher during June - August than during May. The modal class of drop size has an average diameter of 1.116 and 1.912 mm. Both exponential and log-normal distribution seem to be fitting well with the DSD. The rain rate derived from the moment 3.67 (m3.67) of the moment generating function (MGF) of the lognormal distribution function agrees reasonably well with the disdrometer measured rain rate for both the seasons considered. The variability of rain rate, in one minute interval, clearly reveals how the radar derived rainfall accumulation may go wrong even presuming that one uses a perfect Z – R relationship. This suggests the need for understanding the DSD and the micro-physical processes that cause the variability of concentration of drops more precisely to estimate the rain rate and warns about the need for very frequent low elevation radar scans for estimating the rain accumulation.